2000
DOI: 10.3168/jds.s0022-0302(00)75125-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reproductive Performance in Lactating Dairy Cows with Prostaglandin F2, Gonadotropin-Releasing Hormone, and Timed Artificial Insemination

Abstract: Nine hundred and twenty Holstein cows from 16 commercial dairy herds to evaluate three systematic breeding protocols: 14-d PGF2alpha, timed artificial insemination (AI), and GnRH-PGF2alpha, relative to AI following estrus detection without hormone intervention. The timed AI protocol involved GnRH, followed by PGF2alpha 7 d later and GnRH again 2 d after PGF2alpha, with AI 6 to 18 h after the second GnRH. The GnRH-PGF2alpha protocol consisted of GnRH followed by PGF2alpha 7 d later. Eight herds relied on visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
29
2
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
10
29
2
5
Order By: Relevance
“…In the current study, pregnancy rates either to the first or overall up to the fourth AI for primiparous and multiparous cows were similar. These results were in agreement with previous studies [29,32].…”
Section: Ma Alnimersupporting
confidence: 94%
“…In the current study, pregnancy rates either to the first or overall up to the fourth AI for primiparous and multiparous cows were similar. These results were in agreement with previous studies [29,32].…”
Section: Ma Alnimersupporting
confidence: 94%
“…In spite of the pregnancy rate being slightly higher in GnRH-PGF 2α protocol than that in PGF 2α -PGF 2α group, there was no significant difference between synchronization protocols. In another study, Jobst et al (2000) obtained similar results by synchronizing the animals with the protocols used in this study. In addition, there was no significant difference in P 4 concentrations among the synchronization methods.…”
Section: Discussionsupporting
confidence: 68%
“…For dairy farming to remain a profitable enterprise, more attention and skill need to be devoted to increasing reproductive efficiency (Jobst et al 2000). Vasconcelos et al (2006) reported that fertility was influenced by many factors including cyclicity, energy balance, heat stress, parity, milk production, diet and diseases.…”
mentioning
confidence: 99%
“…Some studies have reported that first lactation cows have greater PR than second or greater lactation cows after synchronization following Ovsynch (Stevenson and Phatak 2005), while others have reported greater PR in multiparous cows (Jobst et al 2000). Studies have also reported greater fertility due to presynchronization in multiparous, but not primiparous cows (Cartmill et al 2001); however, the present study did not find this.…”
Section: Discussioncontrasting
confidence: 57%